Analysis Implementation of the Article 25 Income Tax Reduction Policy - Fauzi Isnaen; Fauzan Akbar Albastiah (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study analyzes the implementation of the Income Tax Article 25 reduction policy at PT. Sinar Alami Cemerlang. Using a qualitative approach, the research investigates the processes, challenges, and impacts of this tax reduction policy on the company. The findings reveal that PT. Sinar Alami Cemerlang experienced a significant decline in revenue, prompting the need to apply for a tax reduction. Key challenges included issues related to document completeness and understanding the application procedures. Despite these obstacles, the company successfully fulfilled the necessary requirements, resulting in the approval of their tax reduction application. This approval had a positive effect on the company's cash flow, allowing for improved financial management during a challenging economic period. The study emphasizes the importance of understanding tax policies and the benefits they can provide to businesses facing financial difficulties. Furthermore, the research highlights the need for broader outreach and education regarding tax policies to ensure that companies are well-informed about their rights and obligations. Simplifying the application procedures for tax reductions could facilitate compliance and encourage more businesses to take advantage of available tax relief options. Overall, this study underscores the significance of effective communication and support for taxpayers in managing their tax obligations.